2018
DOI: 10.2298/pan160209017f
|View full text |Cite
|
Sign up to set email alerts
|

Business cycle synchronization of a small open EU-candidate country’s economy with the EU economy

Abstract: The objectives of this paper are to empirically identify business cycles in a small open EU-candidate country such as the Republic of Macedonia and to assess the degree of synchronization of the country's business cycle with the cycle of the EU economy. Towards the first objective, we apply linear and non-linear methods for delineating the production gap cycle in the Macedonian economy. As for the second objective, we apply autoregressive methods to assess the size and speed of cyclical adjustment of the Maced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Whereas some new EU members-especially Hungary, Poland, and Slovenia-were able to achieve a higher degree of economic alignment, particularly in terms of GDP, others lagged behind or experienced no synchronization (Darvas and Szapáry 2008). However, there is also some evidence that small EU countries performed better in terms of synchronization (Filipovski et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas some new EU members-especially Hungary, Poland, and Slovenia-were able to achieve a higher degree of economic alignment, particularly in terms of GDP, others lagged behind or experienced no synchronization (Darvas and Szapáry 2008). However, there is also some evidence that small EU countries performed better in terms of synchronization (Filipovski et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…De Grauwe and Ji (2016) mentioned how important it is to calculate the amplitude of cycles. Filipovski, Trpeski, and Bogoev (2018), used data from 1997 to 2012 by employing the HP and Christiano-Fitzgerald (CF) filter. They argued that there is a high degree of synchronization between the cycles of the EU economy and the cycles of a small open EU-candidate country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are authors that analyze the business cycles and have found that the strength of the economic recovery and of the labour market depend importantly on labour productivity. Filipovski, et al, (2017) investigate the degree of synchronization of business cycles in a small open EU-candidate country such as the Republic of Macedonia with the cycle of the EU economy. They apply linear and nonlinear methods for delineating the production gap cycle in the Macedonian economy and autoregressive methods to assess the size and speed of cyclical adjustment of the Macedonian economy to output shocks to the Euro-zone economy.…”
Section: Literature Reviewmentioning
confidence: 99%